Protective Effect of Ellagic Acid on Epididymal Sperms Quality and DNA Deformity in Mature Rats Exposed to Cadmium Chloride - Mohammed A. Obid; Jawad Kadhim Arrak (University of Thi-Qar Journal of agricultural research, 2023)
This study was designed to investigate the protective effect of Ellagic Acid on Epididymal Sperms Quality and DNA Deformity in mature rats exposed to Cadmium Chloride. The experiment includes a total number of Sixty (60) male Albino Wistar rats weighting (180-220 g) were used in this experiment. Their ages ranged between (10-14) weeks. Rats were divided into four equal groups which administrated orally and daily for six weeks as follows: 100mg EA Kg B.wt, 5mg /Kg B.wt Cd, 100mg EA + 5mg Cd Kg B.wt, and tap water for group 1 (T1), group 2 (T2), group 3 (T3) and control group (C) respectively. The experiment was lasted for 6th weeks. Semen samples were collected after 2, 4 and 6 weeks for estimation sperms parameters. The results revealed a significant decrease of Sperm concentration and Sperms Motility in T2 as compared with control increase significantly of Sperm concentration and Sperms Motility in T1 and the results showed a significant increase of Sperms Abnormalities and Sperms Immotility in T2 with a significant decrease of Sperms Abnormalities and Sperms Immotility in T1 as compared with control. Depending on the current results and discussion, Conclusions are: Ellagic acid is an effective antioxidant against the toxic effect of Cadmium chloride on testicular function and Sperm Parameters.